The feasibility of improved data collection methodologies for sports injuries - Finch, C.; Ozanne-Smith, J.; Williams, F. (Monash University Accident Research Centre, 1995)
Sports and recreational injuries are a cost burden on both individuals and society with respect to the duration and nature of treatment, the amount of sports and working time lost, permanent damage and disability, reduced quality of life and monetary costs. This study summarises the existing data collections on sports injuries, and provides the results of a survey of key sports and other relevant professional bodies, to determine the feasibility of establishing improved data collection methodologies for sports injuries in Australia. ISBN 0 7326 0069 3